Spatial and temporal variations of benthic macroinvertebrate communities in lake Kastoria, Nothern Greece - A. Patsia; D. Kemitzoglou; E. Mavromati; V. Tsiaoussi (2023)
Patsia A., D. Kemitzoglou, E. Mavromati, and Tsiaoussi. 2023. Spatial and temporal variation of benthic macroinvertebrate communities in lake Kastoria, Nothern Greece. Poster presentation in the Symposium for European Freshwater Sciences (SEFS 13), Newcastle University, England, 18 -23 June 2023.